Pondering Dysfunctions in Heritage Protection: Lessons from the Theft of the Codex Calixtinus. Issue 1 (23rd April 2014) - Vargas, Michael A.
Abstract: The Codex Calixtinus, the 12th-century manuscript at the heart of Spain's Camino de Santiago, was stolen, hidden for a year, and then found in a trash can wrapped in newsprint and plastic. The extraordinary theft highlights some dysfunctions in cultural heritage thought and practice. Explored here are questions about exemplars and copies, ambiguities in heritage protection law, problems of proprietorship and commercialization of heritage goods, and administrative negligence in the management of heritage assets. The focus is on Spain, but the questions have broad relevance. This article concludes that one way to better protect movable heritage assets like the codex is to recognize them as part of a broad heritage landscape in which their loss or mismanagement means damage to an entire ecosystem of culture and history.